Association between platelet count and 30-day in-hospital mortality among intensive care unit patients with sepsis: a multicenter retrospective cohort study - Wang, Jun; Zhou, Pan; Li, Xin; Zhou, Li; Deng, Zhe (Frontiers in Medicine, 2025)
BackgroundThe relationship between platelet count and sepsis outcomes in intensive care units (ICUs) requires comprehensive investigation through large-scale multicenter studies.MethodsIn this multicenter retrospective cohort study, we analyzed 17,977 sepsis patients from 208 U.S. hospitals (2014–2015) using the eICU Collaborative Research Database v2.0. Analyses were adjusted for demographics, clinical parameters, comorbidities, and treatments. Generalized additive models and two-piecewise linear regression were used to assess the relationship between platelet count and mortality.ResultsA U-shaped relationship was identified with an inflection point at 176 × 10⁹/L. Below this threshold, each 10 × 10⁹/L increase in platelet count was associated with a 6% decrease in mortality risk (adjusted OR 0.94, 95% CI 0.93–0.95, p < 0.0001), while above it, each 10 × 10⁹/L increase was associated with a 1% increase in mortality risk (adjusted OR 1.01, 95% CI 1.00–1.01, p = 0.0153).ConclusionThis large-scale, multicenter retrospective study has made a significant contribution to understanding the association between platelet count and mortality in patients with sepsis in intensive care units. We identified a critical threshold of 176 × 109/L for platelet count and demonstrated a distinct U-shaped relationship with 30-day in-hospital mortality, providing valuable reference criteria for clinical risk stratification.